MEDIA SOSIAL SEBAGAI STRATEGI PENGEMBANGAN LAYANAN PERPUSTAKAAN - Rumani, Sri (Journal of Documentation and Information Science, 2018)
Social media has a positive side that can be utilized for the development of library services that orientated for the benefit of the user. Excellent service based on information and communication technology becomes a challenge for librarian as library driving machine. Therefore librarians must create innovation and creativity outside the comfort zone. The thought of out of the box in the corridor of librarianship is a must for librarians so that the information rights of the librarian can be fulfilled. This paper has the urgency of order advance in information and communication technology can be utilized by the librarians who manage the library, for the benefit of the user. As for the purpose is the librarian can utilize social media to improve the prime service oriented for the interest of the user. The research method used literature study is a series of activities related to library data collection methods, reading and recording and processing library materials. The result of social media Facebook for extension service is significant that the service extension through Facebook has benefits for the user, besides fast, easy, cheap, without having to come to the library and avoid penalty sanction.